Citrus Essential Oils: Current and Prospective Uses in the Food Industry - E.M. Mustafa, Nazik (Recent Patents on Food, Nutrition & Agriculture, 2015)
Citrus essential oils (CEOs) are gaining popularity in the food industry. This review summarises the chemical compositions of citrus essential oils (monoterpenes, sesquiterpenes and oxygenated derivatives) and explores their antimicrobial activities for use as preservatives in addition to highlight their uses as flavouring and antioxidant agents. The myriad uses of these compounds reflect a global trend towards the increased consumption of natural products. However, challenges such as production technologies, oxidation, chemical contamination by pesticides and consumption induced allergic effects still need to be addressed. Patents identified with CEO uses in food processing and those describe techniques of extraction are presented.
Keywords: food